TGF-b Superfamily Cytokine MIC-1/GDF15 Is a Physiological Appetite and Body Weight Regulator - Tsai, Vicky Wang-Wei; Macia, Laurence; Johnen, Heiko; Kuffner, Tamara; Manadhar, Rakesh; Jørgensen, Sebastian Beck; Lee-Ng, Ka Ki Michelle; Zhang, Hong Ping; Wu, Liyun; Marquis, Christopher Peter; Jiang, Lele; Husaini, Yasmin; et al. (PLOS ONE, 2013)
The TGF-b superfamily cytokine MIC-1/GDF15 circulates in all humans and when overproduced in cancer leads to anorexia/cachexia, by direct action on brain feeding centres. In these studies we have examined the role of physiologically relevant levels of MIC-1/GDF15 in the regulation of appetite, body weight and basal metabolic rate. MIC-1/GDF15 gene knockout mice (MIC-1−/−) weighed more and had increased adiposity, which was associated with increased spontaneous food intake. Female MIC-1−/− mice exhibited some additional alterations in reduced basal energy expenditure and physical activity, possibly owing to the associated decrease in total lean mass. Further, infusion of human recombinant MIC-1/GDF15 sufficient to raise serum levels in MIC-1−/− mice to within the normal human range reduced body weight and food intake. Taken together, our findings suggest that MIC-1/GDF15 is involved in the physiological regulation of appetite and energy storage.